Superior Performance in Skilled Golfers Characterized by Dynamic Neuromotor Processes Related to Attentional Focus - Wang, Kuo-Pin; Frank, Cornelia; Tsai, Yen-yu; Lin, Kao-Hung; Chen, Tai-Ting; Cheng, Ming-Yang; Huang, Chung-Ju; Hung, Tsung-Min; Schack, Thomas (Frontiers in Psychology, 2021)
The meshed control theory assumes that cognitive control and automatic processes work together in the natural attention of experts for superior performance. However, the methods adopted by previous studies limit their capacity to provide in-depth information on the neuromotor processes. This experiment tested the theory with an alternative approach. Twelve skilled golfers were recruited to perform a putting task under three conditions: (1) normal condition, with no focus instruction (NC), (2) external focus of attention condition (EC), (3) internal focus of attention condition (IC). Four blocks of 10 putts each were performed under each condition. The putting success rate and accuracy were measured and EEGs were recorded. The behavioral results showed that the NC produced a higher putting success rate and accuracy than the EC and IC. The EEG data showed that the skilled golfers’ attentional processes in the NC initially resembled those in the EC and then moved towards those in the IC just before putting. This indicates a switch from more automatic processes to cognitive control processes while preparing to putt. The findings offer support for the meshed control theory and indicate the dynamic nature of neuromotor processes for the superior performance of athletes in challenging situations.